Microstructural Characteristics of Glass Bead- and Wollastonite-Filled Isotactic-Polypropylene Composites Modified With Thermoplastic Elastomers - DEMİRER, HALİL (WILEY-BLACKWELL, 2010)
Microstructural characteristics of isotactic-polypropylene/glass bead (iPP/GB) and iPP/wollastonite (iPP/W) composites modified with thermoplastic elastomers, poly(styrene-b-ethylene-co-butylene-b-styrene) copolymer (SEBS) and corresponding block copolymer grafted with maleic anhydride (SEBS-g-MA), were investigated. Scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and dynamic mechanical analyses (DMA) showed that the iPP/SEBS and iPP/SEBS-g-MA blends were partially compatible two-phase systems. Well-dispersed spherical GB and acicular W particles without evidence of interfacial adhesion were observed in the iPP/GB and iPP/W binary composites respectively. Contrary to the blends, melt flow rates of the iPP/GB and PP/W composites decreased more with SEBS-g-MA than with SEBS because of enhanced interfacial adhesion with SEBS-g-MA elastomer. The SEM analyses showed that the ternary composites containing SEBS exhibited separate dispersion of the rigid filler and elastomer particles (i.e., separate microstructure). However, SEBS-g-MA elastomer not only encapsulated the spherical GB and acicular W particles completely with strong interfacial adhesion (i.e., core-shell microstructure) but also dispersed separately throughout iPP matrix. In accordance with the SEM observations, the DSC and DMA revealed quantitatively that the rigid filler and SEBS particles in iPP matrix acted individually, whereas the rigid filler particles in the ternary composites containing SEBS-g-MA acted like elastomer particles because of the thick elastomer interlayer around the filler particles. The Fourier transform infrared analyses revealed an esterification reaction inducing the strong interfacial adhesion between the SEBS-g-MA phase and the filler particles. POLYM. COMPOS., 31:1265-1284, 2010. (C) 2009 Society of Plastics Engineers
Keywords: SEBS BLOCK-COPOLYMERS; IMPACT-MODIFIED POLYPROPYLENE; DYNAMIC MECHANICAL-PROPERTIES; WOOD FLOUR COMPOSITES; G-MA ELASTOMERS; TERNARY COMPOSITES; PHASE-STRUCTURE; POLYMER BLENDS; HYBRID COMPOSITES; FRACTURE-TOUGHNESS